Self-efficacy and Attitude of the Teachers of SMAN Kuansing District towards the Utilization of ICT - Hadriana, Hadriana (Journal of Educational Sciences, 2019)
The development of Information and CommunicationTechnology (ICT) has a very big influence on education. With theenactment of the 2013 Curriculum, a technology-based curriculum,teachers as learning agents must continue to equip themselves withknowledge related to ICT. This descriptive study aims to describe andanalyze self-efficacy and attitudes of the teachers of SMAN KuansingDistrict towards the utilization of ICT in learning activities. Obstaclesfaced by the teachers in utilizing ICT and the efforts that have been doneto overcome the obstacles are also discussed. The research data wascollected in August 2018. By using stratified random sampling technique,55 teachers were determined as the sample. The instrument used was aquestionnaire. Then, the questionnaire was analyzed through descriptivestatistics to obtain frequencies and percentages. Finally, it can beconcluded that the average score of self-efficacy of the teachers ofSMAN in Kuansing District in utilizing ICT is 80.6% and the averagescore of their attitudes is 92.8%. It means that their self-efficacy andattitude are in very good levels. Although there are many obstacles facedby teachers in terms of facilities, infrastructure and human resources, theteachers have their own strategies to solve those obstacle.